Determinants of antidementia drug prescription in patients older than 65: A latent class analysis. Issue 4 (17th February 2020) - François, Mathilde; Sicsic, Jonathan; Pelletier‐Fleury, Nathalie
Abstract: Background: Antidementia drugs (cholinesterase inhibitors and memantine) are still widely prescribed despite their controversial effects and 2011 guidelines that no longer encourage their prescription. The objective was to assess which factors remained determinants of antidementia drug prescriptions. Methods: A cross‐sectional study was performed in 2013. Patients suffering from dementia, aged 65 and over, identified in the French national health insurance database were included. Because we anticipated a high correlation between age, comorbidities, and health care use, we first identified the patients' health status by a latent class analysis. Second, we performed adjusted logistic regression models. The explanatory variables were patients' health status, gender, prescription of nonpharmacological treatments (physical and speech therapies), prescription of psychotropic drugs, and access to health care. Results: Among the 3873 patients included, 38% received antidementia drugs. Three latent classes of patients with different health status were identified. Patients with poor health status received significantly fewer antidementia drugs ( P < .001). Patients with speech therapy or antidepressant drugs received significantly more antidementia drugs ( P < .001), whereas patients with physical therapy received significantly fewer antidementia drugs ( P = .006). Conclusion: Antidementia drugs were less likely to be prescribed for patients with poor health status. This result is encouraging for these frail patients who are more vulnerable to the adverse effects of treatments. At the same time, this result encourage targeting specifically patients in good health status for the use of a decision aid, in an attempt to limit prescriptions by involving patients and families.